The Inverse Perovskite Nitrides (Sr3N2/3–x)Sn, (Sr3N2/3–x)Pb, and (Sr3N)Sb: Flux Crystal Growth, Crystal Structures, and Physical Properties. Issue 3 (20th December 2017) - Pathak, Manisha; Stoiber, Dominik; Bobnar, Matej; Ormeci, Alim; Prots, Yurii; Niewa, Rainer; Höhn, Peter
Abstract : Black single crystals with metallic luster of (Sr3 N2/3– x ) E ( E = Sn, Pb) and (Sr3 N)Sb were grown in lithium flux from strontium nitride, Sr2 N, and tin, lead, or antimony, respectively. Nitrogen deficiency in the tin and the lead compound is a result of the higher ionic charge of the tetrelide ions E 4– as compared to the antimonide ion Sb 3– . In contrast to microcrystalline samples from solid state sinter reactions obtained earlier, the flux synthesis induces nitrogen order in the nitrogen deficient tetrelides. The antimony compound crystallizes as inverse cubic perovskite [ a = 517.22(5) pm, Z = 1, space group Pm 3 m, no. 221] with fully occupied nitrogen site, whereas the nitrogen deficient tin and lead compounds exhibit partially ordered arrangements and a certain phase width in respect to nitrogen contents. For the tetrelides, the nitrogen order leads to a cubic 2 × 2 × 2 superstructure [ E = Sn: a = 1045.64(8) pm for x = 0, a = 1047.08(7) pm for x = 0.08; and E = Pb: a = 1050.7(1) pm for x = 0, space group Fm 3 m, no. 225] as derived from single‐crystal X‐ray diffraction data. The metallic tetrelides show diamagnetic behavior, which is consistent with electronic structure calculations. Abstract :